Incidence of acute appendicitis and its relationship to environmental factors, Peru, 2013 - Tejada-Llacsa, Paul J. (2015)
Background: Acute appendicitis is the most common cause of acute surgical abdomen. Despite its frequency, little is known on its epidemiology in Peru. Objectives: To determine the relation between incidence of appendicitis and environmental temperature. Design: Multiple group study. Setting: San Fernando Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material: Records from the Ministry of Health and data from the National Institute of Statistics and Informatics, Lima, Peru. Methods: An ecological study of multiple groups was performed from appendicitis records. Results were analyzed with Pearson coefficient and Poisson regression. Main outcome measures: Incidence of appendicitis and annual average temperature by department and incidence rate ratios (IRR). Results: A positive correlation between temperature and rate of incidence of appendicitis (r = 0.46; p = 0.02) was obtained. In the regression analysis a significant association (p = 0, 01) between incidence rate of appendicitis and environmental temperature (IRR = 1.04, CI: 1.01-1.08) was found. Conclusion: There was direct association between incidence of appendicitis and enviromental temperature.